Unavoidability in U.S. Privacy Law - Moy, Laura (Science and Technology Law Review, 2024)
Why is U.S. privacy law structured the way it is, with a series of sectoral laws rather than a cross-sectoral law or laws? Why does U.S. privacy law protect information shared in certain contexts—such as information shared with an attorney, a healthcare provider, or a financial provider—rather than particular types of information? One possibility is that sectoral laws apply to contexts in which people typically share highly “sensitive” information containing intimate secrets or with the potential to harm them financially or psychologically. But this Article argues that there is something else at play—that in fact, an under-discussed and underappreciated factor has been a key consideration throughout the history of U.S. privacy law: the unavoidability of information sharing. Tracing the development of several areas of sectoral U.S. privacy law over time, this Article shows that as society changed and contexts emerged in which individuals increasingly found they could not avoid sharing information about themselves with other parties, policymakers repeatedly responded by ratcheting up the privacy protections for information shared in those specific contexts. Taking the discussion of unavoidability into the modern era, this Article ties the tradition of unavoidability consideration in U.S. privacy law to lawmakers’ current struggle to craft comprehensive privacy legislation. Recent years have seen widespread recognition that the sectoral approach is no longer adequate in the modern information economy. But legislators struggle to decide whether it is sufficient to focus on facilitating individuals’ control over their data—as U.S. privacy law historically has strived to do—or whether the law should more directly restrict the use of data in certain ways or for certain purposes. This Article argues that the current privacy legislation struggle, and the types of innovative legislative provisions being proposed, can be better explained with the aid of unavoidability analysis